CAUSES AND TYPES OF UNEMPLOYMENT (Conferencea, 2021)
Employment is a very important indicator in macroeconomics. Employment refers to the number of adults (over 16 years of age) of the working-age population who have a job. But not all of the able-bodied population has a job, there are also unemployed. Unemployment is characterized as the number of the adult working-age population who does not have a job and are actively looking for it. The total number of employed and unemployed makes up the labor force. The following article is devoted to discussing unemployment, its types and causes.